Frailty screening should be nursing business: Planning care, not just predicting outcomes - Andrea Taylor (Journal of Perioperative Nursing)
As the surgical population ages, perioperative nurses are increasingly caring for older adults with complex needs. Among this group, the presence of frailty is common, yet it is often not formally identified.